Genotype–Phenotype Correlation in a New Fabry-Disease-Causing Mutation - Agnė Čerkauskaitė; Rimantė Čerkauskienė; Marius Miglinas; Arvydas Laurinavičius; Can Ding; Arndt Rolfs; Lina Vencevičienė; Jūratė Barysienė; Edita Kazėnaitė; Eglė Sadauskienė (Medicina, 2019)
Background: Fabry disease (FD) is a rare X-linked inherited lysosomal storage disorder caused by α-galactosidase A deficiency leading to intracellular glycosphingolipid accumulation. FD manifestation is multisystem, and can differ depending on disease-related genetic variants. Currently, more than 700 different FD-causing mutations have been identified in the human GLA gene. We identified a novel mutation in a Lithuanian family with classical manifestations of Fabry disease, revealing severe effects to the cardiovascular systems of heterozygous women. Case presentation: A 49-year-old woman underwent echocardiography due to progressive dyspnea that lasted seven years, reduced physical activity, and periodic cardiac arrhythmia. Echocardiography revealed left ventricular hypertrophy with normal diastolic function. The patient had experienced acroparesthesia in her upper limbs and abdominal pain since childhood, and in the last decade had experienced mild proteinuria without renal failure. Her renal biopsy was typical for Fabry disease. The patient’s brain magnetic resonance imaging (MRI) (T2 flair) showed white matter hyperintensities lesions. DNA sequencing of the proband, her mother and one of her sons showed a novel GLA gene exon 2 mutation, c.270C>G (p.Cys90Trp). All three patients had decreased α-galactosidase A activity and specific FD manifestations. Conclusions: A novel GLA mutation, c.270C>G (p.Cys90Trp), was found in a Lithuanian family with a classical form of Fabry disease in heterozygous women with predominant cardiac involvement. However, the exact manifestation of this mutation is still unclear as it is newly reported and further research must be done.